Gargling with Lemon Infused Water (Citrus limon) as a natural alternative to balance saliva pH in pregnant women - Sanusi, Iwa; Purnama, Tedi (Journal Center of Excellent : Health Assistive Technology, 2026)
Background: Pregnant women are vulnerable to decreased salivary pH due to hormonal changes, which can lead to oral health issues such as caries, gingivitis, and halitosis. Excessively acidic salivary pH may also affect maternal nutrition and fetal development. Lemon-infused water contains vitamin C and citric acid, which are known to stimulate saliva production and naturally help neutralize oral acidity. Objective: To examine changes in salivary pH before and after gargling lemon-infused water in pregnant women at the KIA Clinic, Kedaung Health Center, in 2025. Method: This study used a quasi-experimental design with a one-group pretest-posttest approach. A total of 30 pregnant women were selected using purposive sampling. Salivary pH was measured before and after gargling using a pH meter. Results: Prior to the intervention, 70% of participants had acidic salivary pH. After gargling, the proportion of participants with acidic pH decreased to 56.66%, while those with neutral pH increased to 43.34%. Conclusion: Lemon-infused water shows potential as a natural alternative to help balance salivary pH and support oral health in pregnant women.